The urban strategic planning in the peripherical regions: the case of Catania (Sicily) - Luca Ruggiero; Luigi Scrofani (European Regional Science Association (ERSA), 2002)
More and more regional development appears as an effect of the role that cities are able to carry out in the territory. This implies reconsidering not only resources which are available to a city but, above all, its ability to organize urban activities and functions. If these considerations have already found careful appraisal in the most developed regions, by means of the renewal of instruments for the strategic planning of cities, it seems still insufficient the use of these new planning instruments in the less developed regions, although their primary role in the processes of local development. In Southern Italy, for instance, the proliferation of financial support from various sources (E.U., National Government and Regional ones), which imposes plans at different scales (the interregional one, the among cities one and the among suburbs one), and the emergence of actors and stakeholders, also within the presence of public order problems and infrastructural deficiencies, constitute a network that bridles and conditions the city activities and functions, on one side, but can also be a set of occasions that - if used - can push the city towards development itineraries, on the other side. With our paper we propose to compare some experiences of strategic planning in the Southern Italy and to analyse the case of Catania (a central city in an Objective 1 region, Sicily), putting in evidence how the new Plans give order to the activities and the functions of the city, trying to achieve one balanced and sustainable development, by means of the recovery of urban identity.
Keywords: 330